Making science beyond the classroom accessible to students - Rennie, Leonie (Springer, 2015)
This chapter is based on the premise that the science students learn at school should enable them to become scientifically literate citizens, irrespective of what their future career ambitions may be. Students are best served by a school science curriculum that equips them with the knowledge, skills, desire and confidence to deal effectively with the science-related issues that arise not only during their school years but in their adult lives as well. They should be able to access science information when needed, assess its relevance, and apply it to the situation or problem at hand (see also Fensham, this volume). To learn to do this, students need to experience explicit connections between the science they learn in school and the science that happens outside of school. This chapter uses three case studies to illustrate how school-community programmes can promote students’ access to science beyond the classroom and contribute to the development of scientific literacy.